Working Group Reports From ITiCSE on Innovation and Technology in Computer Science Education 1999
DOI: 10.1145/349316.349558
|View full text |Cite
|
Sign up to set email alerts
|

Integrating professionalism and workplace issues into the computing and information technology curriculum

Abstract: Educators in computing and information technology (CIT) suggest a need for graduates going into the workplace to have a better understanding of professionalism and workplace issues. It is not enough for graduates to have technical capabilities. They must understand many aspects of CIT as a discipline. They should be aware of the various types of CIT educational programs, different job titles and ffimctions, and some aspects of the employment supply and demand. They should be aware of the need for each computin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In trialing an initial survey directly based on Little et al [26] and Maister [27], we discovered some confounding ambiguities; for example, the item 'Does what it takes to get the job done' was identified as including anything from diligent application focused on crucial tasks to unscrupulous manipulation. Clearly, responses would be highly dependent on the varying interpretations of individual respondents.…”
Section: Building the Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…In trialing an initial survey directly based on Little et al [26] and Maister [27], we discovered some confounding ambiguities; for example, the item 'Does what it takes to get the job done' was identified as including anything from diligent application focused on crucial tasks to unscrupulous manipulation. Clearly, responses would be highly dependent on the varying interpretations of individual respondents.…”
Section: Building the Questionnairementioning
confidence: 99%
“…and suggested some suitable exercises and assessments [26]. The Graduate Attributes Model adopted by the University of Sydney [38] and similar outcomes models elsewhere require programs to develop broad attributes, including professional values, in their students.…”
Section: Attitudes To Assessing Professional Values 51 Measuring Promentioning
confidence: 99%
“…They suggest that programs aimed at developing IS professionals of the future must cover a wide range of skills and assist the integration of these skills in complex environments. Little, Granger et al, (1999) suggest that it is not sufficient for IS graduates to just possess technical capabihties but should be aware of the need for professionals to take responsibility for their work and the importance of appropriate ethical behaviours. They further suggest a need to include these aspects in the curriculum of current IS programmes.…”
Section: Previous Studiesmentioning
confidence: 99%
“…They further suggest a need to include these aspects in the curriculum of current IS programmes. They identify an "industry-academic gap" that leads to dissatisfaction amongst employer groups with IS graduates (Little, Granger et al, 1999).…”
Section: Previous Studiesmentioning
confidence: 99%
“…Further, they suggest, programs aimed at developing IS professionals of the future must cover a wide range of skills and assist the integration of these skills in complex environments. It has been suggested that it is not sufficient for CIT graduates to just have technical capabilities but should be aware of the need for professionals to have responsibility for their work and the importance of appropriate ethical behaviours (Little et al, 1999). They further suggest a need to include these aspects in the curriculum of current CIT programmes.…”
Section: Previous Studiesmentioning
confidence: 99%